Coal flotation in a low-rank carbonaceous mineral using 3-phenyl-1-propanol as a collector reagent. (15th November 2021) - Vilasó-Cadre, Javier E.; Ávila-Márquez, Delia M.; Reyes-Domínguez, Iván A.; Blanco-Flores, Alien; Gutiérrez-Castañeda, Emmanuel J.
Graphical abstract: Highlights: Low rank coal flotation using 3-phenyl-1-propanol as a flotation collector. Flotation performance of low rank coal flotation is enhanced significantly. Clean low rank coal can be effectively recovered using 3-phenyl-1-propanol as collector. 3-Phenyl-1-propanol enhances the surface hydrophobicity of low rank coal. 3-Phenyl-1-Propanol is more effective than common collectors for low-rank coals. Abstract: In the present work, 3-phenyl-1-propanol is proposed as a new collector for coal flotation in a low-rank carbonaceous mineral containing 2.0% of carbon and basic groups predominantly on the surface. Hydroxyl and carbonyl groups, as well as unsaturated carbon chains, were identified by FT-IR. Microflotation tests were conducted to evaluate and compare the effectiveness of the collector proposed with the one obtained using kerosene, diesel and 1-butylamine. Results show that the highest coal recovery is obtained with 3-phenyl-1-propanol. Mineral has a negative zeta potential in the pH range 2–13, but it does not show an isoelectric point. Furthermore, the zeta potential is modified by the collector. After conditioning, signals corresponding to the collector were identified in the mineral surface by FT-IR. A Box-Behnken experimental design was used for optimization of mineral Recovery and Clean Coal Recovery by flotation. Results showed that pH has not a significant effect on the mineral Recovery, however flotation time and volume of 3-phenyl-1-propanol have a significant direct effect. Optimal conditions for mineral Recovery were pH 8.5 and 84.5 µL of collector for 0.5 g of mineral. For Clean Coal Recovery; pH, flotation time and volume of 3-phenyl-1-propanol have a significant effect. Optimal conditions were pH 4.0, flotation time 2.5 min and 87.9 µL of collector for 0.5 g of mineral.